2006
DOI: 10.1155/ijrm/2006/63214
|View full text |Cite
|
Sign up to set email alerts
|

Noise Source Identification of Small Fan‐BLDC Motor System for Refrigerators

Abstract: Noise levels in household appliances are increasingly attracting attention from manufacturers and customers. Legislation is becoming more severe on acceptable noise levels and low noise is a major marketing point for many products. The latest trend in the refrigerator manufacturing industry is to use brushless DC (BLDC) motors instead of induction motors in order to reduce energy consumption and noise radiation. However, cogging torque from BLDC motor is an undesirable effect that prevents the smooth rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Kim et al identified the source of excessive noise in a small fan-motor system for household refrigerators. They investigated an undesirable effect of cogging torque from the BLDC motor, which prevented the smooth rotation 2 Advances in Acoustics and Vibration of the rotor and resulted in noise [5]. Gue et al conducted experimental and numerical investigations on the aerodynamic noise of an axial fan to develop a low noise fan, which was used to cool a compressor and a condenser in the mechanical room of a household refrigerator [6].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al identified the source of excessive noise in a small fan-motor system for household refrigerators. They investigated an undesirable effect of cogging torque from the BLDC motor, which prevented the smooth rotation 2 Advances in Acoustics and Vibration of the rotor and resulted in noise [5]. Gue et al conducted experimental and numerical investigations on the aerodynamic noise of an axial fan to develop a low noise fan, which was used to cool a compressor and a condenser in the mechanical room of a household refrigerator [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies were limited to bladed-discs and not complete shaftlines. Note that there is significant literature on torsional rotordynamics that did not include the interaction of blading, including that by EPRI, Y-han Kim, Bai, and Bovsunovskii [19][20][21][22].…”
Section: Complexities and Limitations In Modellingmentioning
confidence: 99%
“…The use of an alternating-current motor coupled to a servo drive for the rotation and torsional excitation of small test rotors has been investigated previously [10]. The cogging torque of brushless direct-current (DC) motors has also been used for torsional excitation [11,12]. A DC motor and a digital control system for the rotation and torsional excitation of the test rotor were considered in the current work.…”
Section: Introductionmentioning
confidence: 99%